ANALISIS DAN PERANCANGAN SISTEM INFORMASI MEDIA PENAMPUNG SARAN DAN KELUHAN WAJIB PAJAK PADA UNIT PELAYANAN PAJAK DAERAH CIRACAS - Elis Sondang Dasawati, S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2018)
Within Ciracas Tax Unit Services, the distribution process of information to tax obligatory still executed by SMS services. Therefore SMS application which give ease to employee for distributing information through SMS is necessary. Ciracas Tax Unit Service did not have depository of media Suggestions and Complaints as well. This suggestions and complaints had its importance for improving their quality of services. This depository of media suggestions and complaints information systems using SMS Gateway was developed by using language program of PHP and Mysql for its DBMS. In terms of gateway beetween computer and modem, gammu is used. This SMS gateway application will be use to manage incoming and outcoming messages like complaints and suggestions from tax obligatory for instance. In this research , data collection was done by interviewing and direct observation by researcher. Within Ciracas Tax Unit Services area, In terms of distributing information through SMS and depositoring tax obligatory complaints and suggestion are still using convetional ways. This research, resulted in a SMS gateway information systems program for distributing information through SMS in effective and efficient ways, as well as being depository of tax obligatory complaints and suggestions. From this research, it can be concluded that this SMS Gateway information systems is very helpful for rapidly distributing information through SMS by services staff. Also This system could be good depository of complaints and suggestion that can provide clear and detail reports. For advice terms, make sure all devices that needed in this SMS Gateway information systems is properly installed and doing a regular maintainance for this system.Keywords : Information System, SMS Gateway, Ciracas Tax Unit Services, Complaints,Suggestions